تحليل التعليم المتمايز في تعليم اللغة العربية في الصف الخامس عرفة بالمدرسة الابتدائية الإسلامية النيزام ميدان - Farhani, Dinda (Darul Yasin Al Sys, 2025)
The research aims to understand and analyze the process of differentiated learnng in teaching the Arabic language in the fifth-grade class of Arafah at the Nizam Medan Islamic Elementary School. The research method used by the researcher in this study is descriptive-analytic research. The data is then analyzed qualitatively. The variables of this research are differentiated learnng and Arabic language teaching. The methods used for data collection are interviews and observations. The data analysis method used is the Miles and Huberman method. The results of the research show the following: 1) The way differentiated learnng is applied in teaching Arabic in the fifth-grade Arafah class at the Nizam MIdan Islamic Elementary School is by first selecting the subject matter based on criteria that align with the learning needs of the students, according to facts and ease of understanding. After that, the teacher divides the students into several groups according to their learning needs map. The teacher then guides the students using teaching tools to produce their learning outcomes. 2) The process of teaching Arabic using differentiated learnng has become a more vibrant and enjoyable learning experience. Students feel appreciated and free to learn. Differentiated learnng meets the learning needs of the students.